PENGARUH DISIPLIN KERJA TERHADAP KINERJA PEGAWAI PADA UPTD PUSKESMAS HILISIMAETANO KECAMATAN MANIAMOLO KABUPATEN NIAS SELATAN - Erika Mardiana Dachi (Jurnal Ilmiah Mahasiswa Nias Selatan, 2023)
The purpose of this study was to determine the effect of work discipline on employee performance at the UPTD Hilisimaetano Health Center, Maniamolo District, South Nias Regency. The type of research used is the quantitative type, while the data source is from employees, with the population and sample in this study being 49 respondents. Data collection techniques are research instruments or questionnaires. The data analysis method used is a simple linear regression analysis. The results of this study showed that the calculated value was 6,138>table 1,678. This research can be concluded that there is a significant influence on the performance of employees at the UPTD Hilisimaetano Health Center, Maniamolo District, South Nias Regency. The suggestion of this study is To increase the presence of employees so that consistency in work, an oral reprimand is given for employees who are not present at a predetermined time, if there is no response to the reprimand, a written warning letter is given to the employee